Regulating fertility treatment in Malaysia / Abdullah Ali and Mimi Zalwani Zakaria - Ali, Abdullah; Zakaria, Mimi Zalwani (Faculty of Law, 2014)
Fertility treatment is one of the options available for treat childless couple. However, there is no law pertaining to fertility treatment. This research will analyze the issues pertaining to fertility treatment in Malaysia and compare the position of Australia with regards to their current law in regulating fertility treatment. This study will also suggest some recommendation to regulate fertility treatment in Malaysia. A qualitative research is conducted. Generally, Malaysia does not have any comprehensive law or regulation pertaining to fertility treatment. Fertility treatment involves with legal and ethical issue because it is directly dealing with human sentimental. This study will look into how the law was dealing with the issue pertaining to regulating premises, personnel and public. The aim of the law to regulate the premises, personnel and public from doing the unethical and illegal action relating to the fertility treatment. The Victorian Assisted Reproductive Treatment Act 2008 will be used as a benchmark for best practices. Furthermore, this study can be a platform for respective bodies to come up with some proper law and regulation to fertility treatment.